Use of pcr-rflp of thefla a gene for detection and subtyping of Campylobacter jejuni strains Potentially related to Guillain-barré syndrome, isolated from humans and animals - Scarcelli,E. (2009)
The objectives of the present study were the subtyping of Campylobacter jejuni subsp. jejuni strains obtained from humans and different animal species using PCR-RFLP, and the detection, by means of the same technique, of strains related to serotype PEN O19:LIO 7, the main C. jejuni serotype linked to Guillain-Barré Syndrome (GBS). Seventy C. jejuni strains isolated from human feces (n=33), primates (n=15), dogs (n=5), swine (n=2), bovines (n=1), abortion material from goats (n=2) and poultry carcasses (n=12), all collected in the state of São Paulo, were subtyped by means of PCR-RFLP of fla A gene, using restriction endonucleases Hae III, Afa I and Mbo I. Seven subtypes were observed when using the enzyme Hae III; eight when using Mbo I; and seven when using Afa I. The combination of the three endonucleases led to 16 fla-RFLP subtypes, from which ten subtypes shared strains of human and animal origin. From these, seven subtypes were observed in human and broiler strains. In eight subtypes, the other animal species shared patterns with human strains. It was inferred that, besides broilers, swine, goats, dogs and primates may be sources of infection for human in São Paulo. PCR-RFLP is a highly discriminatory technique that may be applied to molecular epidemiology studies of samples from different origins. Besides, the study also enabled the detection of two human strains and two primate strains related to serotype PEN O19: LIO 7.